2018
DOI: 10.1007/s42247-018-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen fillers for reinforcing and strengthening of epoxy composites

Abstract: Pollen grains have the potential to be effective plant-based biorenewable fillers in polymer matrices due to their high modulus, strength, chemical stability, and unique nanoscale architectures. In this work, we present evidence for the effectiveness of pollen as a reinforcing filler in epoxy matrices, characterized as a function of pollen loading and surface treatment. Composites prepared with unmodified native defatted ragweed pollen (D) displayed decreased mechanical properties and increasing glass transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This behavior can constitute a limitation in several applications. A possible improvement of the elongation and impact properties could be achieved with filler surface treatments or by the addition of an adhesion promoter additive . As expected, these treatments involve an increase in the costs and the possibility of a no longer biodegradable composite.…”
Section: Resultsmentioning
confidence: 93%
“…This behavior can constitute a limitation in several applications. A possible improvement of the elongation and impact properties could be achieved with filler surface treatments or by the addition of an adhesion promoter additive . As expected, these treatments involve an increase in the costs and the possibility of a no longer biodegradable composite.…”
Section: Resultsmentioning
confidence: 93%
“…The resulted polymer -pollen composite showed an 80% increase in tensile strength and a wider glass transition [2]. Similarly, ragweed pollen were recently reported to result in a 47% increase in tensile strength, a 70% increase in strain at break and a 14% increase in modulus of epoxy composites at 10 wt% pollen loading [3]. Uddin et al [4,5] have demonstrated the oral delivery of vaccines to mice via ragweed pollen and the potential for pollen to be used for controlled release of pharmaceuticals has been reviewed [6].…”
Section: Introductionmentioning
confidence: 61%
“…Composites are applied in a wide range of applications because of their promising properties [117][118][119][120][121][122][123][124][125]. To illustrate, the corrosion behavior of BCN films has been attracted a growing attention of researchers to allow their application in different environments.…”
Section: Corrosion Studiesmentioning
confidence: 99%